La evaluación del proceso de descentralización en Santiago de Chile - Guerra Rodríguez, Carlos (América Latina Hoy, 2009)
RESUMEN: Trás presentar el contexto creado por la Reforma Administrativa del Régimen Militar en Chile, se identifica la problemática que lleva a impulsar la Reforma Comunal de la provincia de Santiago. Se consideran objetivos, estrategias, localización, proceso, calendario y desarrollo de esta Reforma. Por último, se evalúa el alcance. ABSTRACT: After explaining the context created by the Administrative Reform of the Military Regime in Chile. The author identifies the problematic aspects which impulsed the communal reform in the Province of Santiago. In the article are considerated objectives, strategies, localizations, process, timing. and development of this reform. At the end. there is also an evaluation of its scope.